„Jaka, sądzisz, jest biblia cygańska?” – charakterystyka op. 57 Mieczysława Wajnberga śladem Dymitra Szostakowicza - Nowok-Zych, Agnieszka (Res Facta Nova, 2021)
Opus 57 by Mieczysław Weinberg is undoubtedly one of the most beautiful and interesting vocal cycles in the composer’s oeuvre. The Gypsy Bible is closely linked to two figures Weinberg regarded as his masters: Julian Tuwim in the field of words, and Dmitri Shostakovich in the field of musical strategies. Verena Mogl in her publication “Juden die ins Lied sich retten” – der Komponist Mieczysław Weinberg (1919–1996) in der Sowjetunion draws attention to the mostly hidden or veiled references to the life and works of Shostakovich. They become the key to interpreting the cycle both in the context of the relationship between the authors and the political situation prevalent at that time. The article presents the most important threads concerning the biographical and artistic kinship between Weinberg and Tuwim, as well as the issues indicated by Verena Mogl, probably unknown to Polish readers. The appendix attached to the article contains all of Tuwim’s poems used in The Gypsy Bible along with the formal structure given to them by the composer. This is a new contribution to research on the creative output of Mieczysław Weinberg.